Efektivitas Model Teams Games Tournament Berbantuan Game Monopoli dalam Meningkatkan Hasil Belajar dan Keaktifan Siswa Kelas VII di SMP Negeri 48 Samarinda - Rosinta Rosinta; Vandalita Maria Magdalena Rambitan; Dora Dayu Rahma Turista; Suparno Putera Makkadafi; Nelda Anasthasia Serena (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effectiveness of the team games tournament learning model assisted by the monopoly game in improving student learning outcomes and activeness in the material of classification of living things for grade VII at SMP Negeri 48 Samarinda. The selection of this school was based on the problems found, namely the learning process that still tends to be teacher-centered, low student participation in learning activities, and the existence of a school policy that does not allow students to bring mobile phones, thus limiting the use of digital learning media in the classroom. The method used was a quasi-experiment with a pretest–posttest control group design, with samples determined through cluster random sampling techniques, so that two classes were obtained, namely the experimental class and the control class, each consisting of 24 students. The research variables included cognitive learning outcomes and student activeness, with instruments in the form of tests (pre-test and post-test) and an activeness questionnaire. Data analysis was carried out using normality tests, homogeneity tests, and independent sample t-tests. The results showed that the average pre-test scores for both classes were relatively similar, while the average post-test scores for the experimental class were higher than those for the control class. The percentage of student activity in the experimental class was in the very active category, while the percentage of student activity in the control class was in the active category. The t-test results showed a significance value of 0.000 < 0.05, indicating a significant difference between the two classes. Thus, the Monopoly game-assisted team games tournament learning model is effective in improving student learning outcomes and engagement.